Cervical cancer screening in patients at a tertiary care centre with Pap smear and HPV DNA testing - Shinde, Khushboo Suresh; Kochar, Swati; Nayak, Asmita; Gupta, Anjli; Soni, Chandni; Charan, Bhawana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Cervical cancer ranks fourth among the most commonly diagnosed cancers as well as the fourth leading cause of cancer mortality in women globally. Of all new cases and deaths worldwide in 2020, India accounted nearly one-fourth of deaths due to cervical cancer. In India, cervical cancer is the second most common cancer in both incidence 18.3% and cancer mortality 18.7% among women in 2020, with a 5-year prevalence of 18.8%. Methods: A hospital based cross sectional study was conducted in the Gynecology OPD of PBM Hospital, Bikaner. 118 women aged 19-60 years presenting with complaints such as unusual bleeding between periods/after menopause/after sexual intercourse; increased or foul-smelling vaginal discharge etc were included. A questionnaire was administered containing general information, clinical findings at pelvic evaluation. They then underwent Pap smear, HPV testing and histo-pathology. Appropriate statistical tests were used to compare the outcome between the sub-groups. Results: Pap smear offered high specificity (~93.9%) and a strong NPV (99.1%), with a low positive predictive value (PPV~18%-25%) indicating a high false-positive rate, necessitating triage with confirmatory tests. HPV DNA testing emerged as the superior tool, with 100% sensitivity and NPV. Its specificity was over 95% and PPV was 37.5%. Conclusions: HPV DNA testing is the most accurate screening test, reflecting its utility in early detection of high-risk cases.